Beyond Bitcoin : the economics of digital currencies and blockchain technologies - Halaburda, Hanna (Palgrave Macmillan, 2022)
Over the last few years, we have witnessed an upsurge of enthusiasm about cryptocurrencies and, more generally, the so-called blockchain technology. In this new and updated edition, the authors explore what exactly these new technologies entail and promise. They argue that to understand the potential challenges and further developments in the market, one needs to develop an understanding of what needs these innovations fulfill and what business models are consistent with their use. For that, we need to sufficiently understand both the technology and how it affects the economic forces at play. This book goes beyond the headlines that say blockchain will decentralize everything and provides in-depth, rigorous analysis of what can be effectively decentralized and how this decentralization will work. The book draws not only on the general knowledge of digital currencies and blockchain technologies, but also on recent academic research on the topic. Featuring a fully updated chapter on cryptocurrencies and new chapters on smart contracts and enterprise blockchains, this book is critical reading for those interested in how technology developments impact business and society. Hanna Halaburda is Associate Professor of Technology, Operations and Statistics at the Stern School of Business at New York University, USA. Previously, she was on an assistant professor at Harvard Business School, USA; a visiting scholar at Columbia University, USA; and a senior economist at the Bank of Canada. Her research specializes in the economics of digital currencies, platform competition, and the impact of technology on firms' strategy. Miklos Sarvary is the Carson Family Professor of Business at Columbia Business School, USA, where he serves as Faculty Director of the Media and Technology Program. Previously, he was on the faculty at Stanford University, USA; Harvard University, USA; and INSEAD. His research has focused on information and news markets, social network competition and, more recently, online advertising effectiveness. Guillaume Haeringer is Associate Professor at the Zicklin School of Business at Baruch College, USA. Previously he was visiting faculty at Stanford University, USA; on the faculty at the Universitat Autonoma de Barcelona, Spain; lecturer at the University of Warwick, UK. His research focuses on market design, matching theory, game theory and the economics of cryptocurrencies.